2020
DOI: 10.3389/fnins.2020.00910
|View full text |Cite
|
Sign up to set email alerts
|

Potential Pathways for Circadian Dysfunction and Sundowning-Related Behavioral Aggression in Alzheimer’s Disease and Related Dementias

Abstract: Patients with Alzheimer's disease (AD) and related dementias are commonly reported to exhibit aggressive behavior and other emotional behavioral disturbances, which create a tremendous caretaker burden. There has been an abundance of work highlighting the importance of circadian function on mood and emotional behavioral regulation, and recent evidence demonstrates that a specific hypothalamic pathway links the circadian system to neurons that modulate aggressive behavior, regulating the propensity for aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 193 publications
(250 reference statements)
0
28
0
Order By: Relevance
“…The most studied and clinically used therapy is light therapy for sundowning patients, although, in some cases, the SCN may be too degenerated for light therapy to be effective [308]. One study reported that a non-invasive 40 HZ light flicker was sufficient to ameliorate the AD-associated rhythmic disruption in mice [309]. Sundowning severity increases as AD progresses, and light is sometimes recommended during the evening hours to reduce associated agitation.…”
Section: Sundowning Syndromementioning
confidence: 99%
“…The most studied and clinically used therapy is light therapy for sundowning patients, although, in some cases, the SCN may be too degenerated for light therapy to be effective [308]. One study reported that a non-invasive 40 HZ light flicker was sufficient to ameliorate the AD-associated rhythmic disruption in mice [309]. Sundowning severity increases as AD progresses, and light is sometimes recommended during the evening hours to reduce associated agitation.…”
Section: Sundowning Syndromementioning
confidence: 99%
“…Loss of cognitive functions in the early stage of dementia is highly associated with neuronal death boosted by the crosstalk between peripheral and CNS inflammation [44, 45], which includes different mechanisms such as vagal reflex-induced inflammation from the periphery to the brain [46, 47], blood-brain barrier disruption [13], and direct entry of peripheral immune cells into the brain parenchyma [12]. Decline of noncognitive functions has been related to changes in anatomic structures [48], circadian rhythm dysfunction [49], metabolic changes [50], and imbalance in the production of neurotransmitters [51, 52], but less is known about how much systemic inflammation aggravates noncognitive symptoms. Hence, our results open a debate on whether there is an underlying mechanism that produces a negative feedback in leukocytes, especially in late stages of dementia with BPSD, making leukocytosis values a reliable biomarker to identify CNS inflammation and damage at the time of BPSD onset.…”
Section: Discussionmentioning
confidence: 99%
“…However, circadian rhythms are markedly disturbed in AD all through the disease course. Day-time agitation, night insomnia, restlessness and sun-downing are among the (Todd, 2020). AD is often associated with changes in the physiological parameters of sleep that include decrease in total sleep time and efficiency, prolonged sleep time stage 1 and stage 2 sleep, lesser time in deeper sleep, increased REM sleep latency and decreased REM sleep, together with decreased density of eye movement activity (Weldemichael and Grossberg, 2010).…”
Section: Ad and Sleep Disturbancesmentioning
confidence: 99%
“…Day-time agitation, night insomnia, restlessness and sun-downing are among the characteristic changes observed in AD and they worsen with AD progression to affect around 42–52% of AD patients. Such sleep changes are majorly attributed to disruptions in the precise cascade of circadian rhythm (Todd, 2020 ).…”
Section: Ad Sleep Disorders and Circadian Rhythmmentioning
confidence: 99%